Discriminating between models of ambiguity attitude: a qualitative test - Mukerji, S; Cubitt, R; van de Kuilen, G (University of Oxford, 2014)
The exchange between Epstein (2010) and Klibanoff et al. (2012) identified a behavioral issue that sharply distinguishes between two classes of models of ambiguity sensitivity, exemplified by the ?-MEU model and the smooth ambiguity model, respectively. The issue in question is whether a subject